The Effectiveness of ASIAP Digital Innovation in the Management of SPPT PBB in Pekanbaru City: DAIGUSI Analysis of Innovation and User Satisfaction - Rizqi, Ikra Novar; Dytihana, Zahra Aqilah (Knowbase : International Journal of Knowledge in Database, 2025)
Digital innovation in public services is increasingly becoming a primary need for efficient and responsive governance. One such innovation is ASIAP (Aplikasi Antar SPPT PBB), a digital system developed by the Pekanbaru City Regional Revenue Agency (Bapenda) to distribute Tax Payable Notification Letters (SPPT) online. However, as a silent innovation, ASIAP is not widely known, despite its significant contribution to regional tax management. This study aims to assess user satisfaction with the ASIAP application and analyze the accompanying innovation diffusion process. The study used a mixed-method approach with quantitative and qualitative methods. Data collection was conducted by distributing questionnaires to ten ASIAP user employees, based on five dimensions in the End-User Computing Satisfaction (EUCS) model: content, accuracy, format, ease of use, and timeliness. In-depth interviews were also conducted with several Bapenda employees to explore the innovation adoption process based on Rogers' innovation diffusion theory. The results showed that users found the ASIAP application quite satisfactory, particularly in terms of information accuracy and ease of use. However, aspects of information up-to-dateness and visual presentation still require improvement. The ASIAP diffusion process is considered to have progressed gradually through five stages of innovation adoption, supported by the role of internal change agents and informal communication between employees. In conclusion, ASIAP is a potential digital innovation for strengthening information technology-based public services at the regional level, but it still requires further development to achieve broader and more equitable benefits.